Optimal Redistributive Taxation in a Search Equilibrium Model - Mathias Hungerbühler; Etienne Lehmann; Alexis Parmentier; Bruno van der Linden (Institute for the Study of Labor (IZA), 2005)
This paper characterizes optimal non-linear income taxation in an economy with a continuum of unobservable productivity levels and endogenous involuntary unemployment due to frictions in the labor markets. Redistributive taxation distorts labor demand and wages. Compared to their efficient values, gross wages, unemployment and participation are lower. Average tax rates are increasing. Marginal tax rates are positive, even at the top. Finally, numerical simulations suggest that redistribution is much more important in our setting than in a comparable Mirrlees (1971) setting.
Keywords: J64; H21; D82; H24; 330; optimal income taxation; unemployment; wage bargaining; matching; Einkommensteuer; Einkommensumverteilung; Optimale Besteuerung; Arbeitslosigkeit; Lohnverhandlungen; Matching; Theorie